Educational and Organizational Interventions to Improve the Usefulness of Clinical Pharmacological Advice for Personalized Drug Dosing Based on Therapeutic Drug Monitoring. (3rd May 2014) - Pea, Federico; Dose, Lucia; Cojutti, Piergiorgio; Baraldo, Massimo; Fontana, Fabrizio; Favaretti, Carlo; Furlanut, Mario
Abstract This study was aimed at increasing the clinical usefulness of clinical pharmacological advice (CPA) for personalized drug dosing based on therapeutic drug monitoring (TDM). Educational and organizational interventions focused on improving the knowledge of clinical pharmacology among hospital healthcare workers and reducing the incidence of errors throughout the process were planned. After a pre‐interventional period of risk assessment, different list forms of the types of error occurring in the various phases of the process (Phase 1, request for CPA and blood sampling for TDM; Phase 2, sample delivery to and check in at the CPU; Phase 3, TDM execution and CPA production) were created. In the interventional period, the errors were collected daily and educational programmes were carried out. The pre‐intervention error rate was 19.5%, and resulted significantly higher for the requests coming from the medical wards compared with those from the surgical wards or the ICUs (26.0% versus 10.5% versus 13.7%, p < 0.001). The educational programme trained 303 nurses and 145 physicians. Afterwards, the error percentage progressively dropped (15.5% in the 2nd trimester; 12.3% in the 3rd one; 10.5% in the 4th one). The adopted strategy resulted in significant improvements which may be useful both to improve quality of patient care and to reduce waste in healthcare costs.